Organizing for Societal Grand Challenges. - Gümüsay, Ali Aslan. (Research in the Sociology of Organizations Series, 2022)
The ebook edition of this title is Open Access and freely available to read online. Organizing for Societal Grand Challengesunpacks how diverse forms of organizing help tackle-or reinforce-grand challenges,while emphasizing the need for researchers to expand their methodological repertoire and reflect upon scholarly practices.